TB case management at community level: situation of the treatment completed patients in women's health and development programme - Islam, Md. Nazrul; Mahmud, Shah Noor; Ali, Ahmed; Fazlul Karim (BRAC Research and Evaluation Division (RED), 2019)
The Women's Health and Development Programme (WHOP) of BRAC initiated a community based tuberculosis {TB) control programme in 10 thanas in June, 1992 to complement and supplement the government TB control programme. The Research and Evaluation Division conducted a study on 181 TB patients who completed the anti-TB treatment on or before June, 1993 to investigate their a) socioeconomic and physical condition and b) measures taken for the patients who had cough for more than four weeks after completion of treatment. The study was conducted in all 10 thanas of WHOP in July 1994 and data· was collected from 181 patients administering a pretested questionnaire. About 72.0% of ~he patients were male indicative that the males are suffering from TB more than female or their morbidity is more reported than the female. Similar results were also found in national prevalence survey in 1987. Almost 67.0% of the patients came ·from target · group {TG), possibly the programme was more focused to the TG families. Moreover, 65.0% of the patients were treated with 12 months, 16.6% with six months, 17.7% with eight months and 1.1% with nine months treatment regimens. Sputum of 5 patients (2.8%) were found to be bacteriologically positive after one month completion of treatment. Moreover, a total of 9 patients died within one year after completion of treatment, but the causes of three deaths were found to be confirm~d (cancer, madness and suicide). Forty (24.4%) of ~he surveyed patients complained of history of cough for more than 4 weeks but 52.5% of them did not take any treatment, while sputum was examined for 32.5% of the cases.